Association between maternal adiposity measures and infant health outcomes: A systematic review and meta‐analysis. (8th July 2022) - Nguyen, Giang; Hayes, Louise; Ngongalah, Lem; Bigirumurame, Theophile; Gaudet, Laura; Odeniyi, Adefisayo; Flynn, Angela; Crowe, Lisa; Skidmore, Becky; Simon, Alexandre; Smith, Vikki; Heslehurst, Nicola
Summary: Maternal obesity increases risks of adverse fetal and infant outcomes. Guidelines use body mass index to diagnose maternal obesity. Evidence suggests body fat distribution might better predict individual risk, but there is a lack of robust evidence during pregnancy. We explored associations between maternal adiposity and infant health. Searches included six databases, references, citations, and contacting authors. Screening and quality assessment were carried out by two authors independently. Random effects meta‐analysis and narrative synthesis were conducted. We included 34 studies ( n  = 40, 143 pregnancies). Meta‐analysis showed a significant association between maternal fat‐free mass and birthweight (average effect [AE] 18.07 g, 95%CI 12.75, 23.38) but not fat mass (AE 8.76 g, 95%CI −4.84, 22.36). Women with macrosomic infants had higher waist circumference than controls (mean difference 4.93 cm, 95% confidence interval [CI] 1.05, 8.82). There was no significant association between subcutaneous fat and large for gestational age (odds ratio 1.06 95% CI 0.91, 1.25). Waist‐to‐hip ratio, neck circumference, skinfolds, and visceral fat were significantly associated with several infant outcomes including small for gestational age, preterm delivery, neonatal morbidity, and mortality, although meta‐analysis was not possible for these variables. Our findings suggest that some measures of maternal adiposity may be useful for risk prediction of infant outcomes. Individual participant data meta‐analysis could overcome some limitations in our ability to pool published data.